Methodological Proposal for Strength and Power Training in Older Athletes: A Narrative Review - Jofré-Saldía, Emilio; Villalobos-Gorigoitía, Álvaro; Gea-García, Gemma (Current Aging Science, 2022)
Introduction: Within the adult population, it is not uncommon to meet older athletes who challenge the negative stereotypes associated with aging. Although their physical performance is superior to their sedentary counterparts, they are not immune to impaired neuromuscular function, leading to a decreased physical capacity and an increased risk of injuries. Despite the abundant information about the benefits of strength/power training in advanced ages, there are no methodological proposals that guide physical activity professionals to program this type of training. Objective: This study aimed to review the factors related to the decrease in sports performance within older athletes and the benefits of a strength/power program in order to provide a methodological proposal to organize training in this population. Methods: This is a review article. First, databases from PubMed, Science Direct, and SPORTSDiscus and search engines, namely Google Scholar and Scielo, were reviewed, using standard keywords such as strength and power training, evaluation of physical performance, neuromuscular function, and risk of injury in the elderly athlete. All related articles published during the period 1963 to 2020 were considered. A total of 1837 documents were found. By removing 1715 unrelated documents, 122 articles were included in the study after revision control. Results: Strength/power training is key to alleviating the loss of performance in older athletes and the benefits in neuromuscular function, which helps reduce the rate of serious injuries, maintaining sports practice for a longer period of time. In order to design an appropriate program, a prior evaluation of the individual’s physical-technical level must be carried out, respecting the biologicalpedagogical principles and safety regulations. Conclusion: The methodological proposal delivered in this review can serve as a technical guide for physical activity professionals, which will be able to structure the strength/power training and thus preserve the sports practice in older athletes for a longer time.
Keywords: risk of injury